International Students Celebrate at Convo - Borneo, Sunday Post (Borneo Sunday Post, 2014)
Out of 1200 graduates in AeU 4th Convocation, 300 are international students, and among them was a new batch of Indonesian students who graduated from Bachelor of Information & Communications Technology (Hons) programme, which is a joint collaboration between AeU and the State Polytechnics of Jakarta, Indonesia.